Assessment of SARS-CoV-2 Immunity in Convalescent Children and Adolescents - Tsang, Hing Wai; Chua, Gilbert T.; To, Kelvin K. W.; Wong, Joshua S. C.; Tu, Wenwei; Kwok, Janette S. Y.; Wong, Wilfred H. S.; Wang, Xiwei; Zhang, Yanmei; Rosa Duque, Jaime S.; Chan, Godfrey C. F.; Chu, Wai Kit; et al. (Frontiers in Immunology, 2021)
Persistence of protective immunity for SARS-CoV-2 is important against reinfection. Knowledge on SARS-CoV-2 immunity in pediatric patients is currently lacking. We opted to assess the SARS-CoV-2 adaptive immunity in recovered children and adolescents, addressing the pediatrics specific immunity towards COVID-19. Two independent assays were performed to investigate humoral and cellular immunological memory in pediatric convalescent COVID-19 patients. Specifically, RBD IgG, CD4+, and CD8+ T cell responses were identified and quantified in recovered children and adolescents. SARS-CoV-2-specific RBD IgG detected in recovered patients had a half-life of 121.6 days and estimated duration of 7.9 months compared with baseline levels in controls. The specific T cell response was shown to be independent of days after diagnosis. Both CD4+ and CD8+ T cells showed robust responses not only to spike (S) peptides (a main target of vaccine platforms) but were also similarly activated when stimulated by membrane (M) and nuclear (N) peptides. Importantly, we found the differences in the adaptive responses were correlated with the age of the recovered patients. The CD4+ T cell response to SARS-CoV-2 S peptide in children aged <12 years correlated with higher SARS-CoV-2 RBD IgG levels, whereas higher level of CD8+ T cells in children aged ≥12 years, suggesting the importance of a T cell-dependent humoral response in younger children under 12 years. Both cellular and humoral immunity against SARS-CoV-2 infections can be induced in pediatric patients. Our important findings provide fundamental knowledge on the immune memory responses to SARS-CoV-2 in recovered pediatric patients.